Improving the Motivation of Students in Arabic Language Learning through Learning Management System - Moh. Fery Fauzi; Irma Anindiati (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2021)
Learning Arabic language for novice students can be something difficult if they do not have a right motivation and teachers do not have a good approach. The Attention, Relevance, Confidence, and Satisfaction (ARCS) model of motivation should be applied to real-world educational settings, including computer-based learning approaches, to find more effective ways of understanding the major influences on learning motivation and for systematic ways of identifying and solving problems with learning motivation. This study aimed to improve the motivation of students in Arabic language learning through learning management system and to improve students’ outcome of Arabic speaking skills. This classroom action research was conducted two cycles (repeated five times). Each cycle referred to Spiral Model by Kemmis, McTaggart, and Nixon. The subjects were 39 students of C Class and D Class in Kalam Ibtida’i Course at academic year 2021-2022 in the Department of Arabic, Faculty of Letters, Universitas Negeri Malang, Indonesia. The data of students’ motivation were obtained from performance grading rubric of the relevance component of the ARCS Model and the data of students’ outcome in Arabic language learning were obtained from students worksheet assesment and end-of-cycle Arabic speaking test. The results showed the improving of: (1) the motivation of students in Arabic language learning through learning management system and (2) the students’ outcome of Arabic speaking skills. This ARCS Model was effectively used for this Kalam Ibtida’I course because novice students need good motivation to learn Arabic speaking skills.